Study of Complexation in Acetone-Chloroform Mixtures by Infrared Spectroscopy. (24th February 2014) - Ilchenko, Oleksii O.; Kutsyk, Andrii M.; Obukhovsky, Vyacheslav V.
Abstract : FTIR spectra of acetone-chloroform system with various component ratios were investigated within the spectral range 3950–4550 cm −1 . Methods of multivariate curve resolution were applied to decompose the FTIR spectra into specific components of different composition. A method of decomposition based on structural model of solution which contains acetone, chloroform, and complex acetone/chloroform (1 : 1) was proposed. Results of both approaches are in good agreement within the range of measuring error.